Tabla de Transformadas de Laplace
Enviado por Paola FS • 27 de Octubre de 2018 • Apuntes • 277 Palabras (2 Páginas) • 180 Visitas
Tabla de Transformadas de Laplace
L {f(t)} =
Z ∞
0
e
−s t f(t) dt
f(t) F(s) f(t) F(s)
1. 1
1
s
2. t
n
, n = 1, 2, 3, ..
n!
s
n+1
3. t
α
, −1 < α
Γ(α + 1)
s
α+1 4. e
a t 1
s − a
5. t
n
e
a t
, n = 1, 2, 3, ..
n!
(s − a)
n+1 6. sin (ω t)
ω
s
2 + ω2
7. cos (ω t)
s
s
2 + ω2
8. sinh (ω t)
ω
s
2 − ω2
9. cosh (ω t)
s
s
2 − ω2
10. e
a t sin (ω t)
ω
(s − a)
2 + ω2
11. e
a t cos (ω t)
s − a
(s − a)
2 + ω2
12. t sin (ω t)
2 ω s
(s
2 + ω2)
2
13. t cos (ω t)
s
2 − ω
2
(s
2 + ω2)
2
14. sin (ω t) − ω t cos (ω t)
2 ω
3
(s
2 + ω2)
2
15. sin (ω t) + ω t cos (ω t)
2 ω s2
(s
2 + ω2)
2
16. 1
a − b
e
a t − e
b t 1
(s − a) (s − b)
17. 1
a − b
a e
a t − b eb t s
(s − a) (s − b)
18. 1
a
2
(1 − cos (a t)) 1
s (s
2 + a
2)
19. 1
a
3
(a t − sin (a t)) 1
s
2 (s
2 + a
2)
20. f(t) + g(t) F(s) + G(s)
21. c f(t) c F(s) 22. f
0
(t) s F(s) − f(0)
23. f
00(t) s
2 F(s) − s f(0) − f
0
(0) 24. f
(n)
(t) s
n F(s) − s
n−1
f(0) − · · · − f
(n−1)(0)
25. e
a t f(t) F(s − a) 26. t
n
f(t) (−1)n d
n
dsn
F(s)
27. Ua(t) = U(t − a)
e
−a s
s
28. f(t − a)Ua(t) e
−a s F(s)
29. f ∗ g =
Z t
0
f(t − σ)g(σ)dσ F(s) G(s) 30. δ(t − c) e
−c s
31. f(t + T) = f(t)
R T
0
e
−s t f(t) dt
1 − e−s T 32. Z t
0
f(σ) dσ 1
s
F(s)
33. f(t)
t
Z +∞
s
F(σ) dσ 34. f(a t)
1
a
F
s
a
lim
s→+∞
s F(s) = f(0) lim
s→0+
s F(s) = lim t→+∞
f(
...